Novel associations of bile acid diarrhoea with fatty liver disease and gallstones: a cohort retrospective analysis - Appleby, Richard N (BMJ Open Gastroenterol, 2017)
BACKGROUND: Bile acid diarrhoea (BAD) is a common cause of chronic diarrhoea with a population prevalence of primary BAD around 1%. Previous studies have identified associations with low levels of the ileal hormone fibroblast growth factor 19 (FGF19), obesity and hypertriglyceridaemia. The aim of this study was to identify further associations of BAD. METHODS: A cohort of patients with chronic diarrhoea who underwent (75)selenohomocholic acid taurate (SeHCAT) testing for BAD was further analysed retrospectively. Additional clinical details available from the electronic patient record, including imaging, colonoscopy, chemistry and histopathology reports were used to calculate the prevalence of fatty liver disease, gallstones, colonic neoplasia and microscopic colitis, which was compared for BAD, the primary BAD subset and control patients with diarrhoea. FINDINGS: Of 578 patients, 303 (52%) had BAD, defined as a SeHCAT 7d retention value <15%, with 179 (31%) having primary BAD. 425 had an alanine aminotransferase (ALT) recorded, 184 had liver imaging and 176 had both. Overall, SeHCAT values were negatively associated with ALT (r(s)=−0.19, p<0.0001). Patients with BAD had an OR of 3.1 for an ALT >31 ng/mL with imaging showing fatty liver (p<0.001); similar figures occurred in the primary BAD group. FGF19 was not significantly related to fatty liver but low levels were predictive of ALT >40 IU/L. In 176 subjects with gallbladder imaging, 27% had gallstones, 7% had a prior cholecystectomy and 34% either of these. The median SeHCAT values were lower in those with gallstones (3.8%, p<0.0001), or gallstones/cholecystectomy (7.2%, p<0.001), compared with normal gallbladder imaging (14%). Overall, BAD had an OR of 2.0 for gallstones/cholecystectomy (p<0.05). BAD was not significantly associated with colonic adenoma/carcinoma or with microscopic colitis. INTERPRETATION: The diagnosis of BAD is associated with fatty liver disease and with gallstones. The reasons for these associations require further investigation into potential metabolic causes.